Predicting Difficult Laryngoscopy Using Ultrasound Measurement of Distance from Skin to Epiglottis - Shah, Aashish; Kunwar, Bhuban Raj; Limbu, Bishan; Rayamajhi, Mallika; Amatya, Bishow Ram; Acharya, Puspa (Medical Journal of Shree Birendra Hospital, 2025)
Introduction: Management of the difficult airway poses a challenge and identification of difficult airway poses even greater challenges. Conventional methods are used for identifying difficult airway but with little sensitivity and specificity. Use of ultrasound in the assessment of the airway is an emerging technique with increased sensitivity and specificity as compared to conventional techniques. This study aimed to predict difficult airway using ultrasound. Methods: A prospective observational was study was conducted among 138 patients, who were divided into two groups: easy laryngoscopy and difficult group based on the Cormack-Lehane grade (CL grade). Airway assessment of each patient was done with measurement of thyromental distance (TMD), Mallampati grading (MPG), inter-incisor distance (IID) and ultrasonographic measurement of the distance between skin to epiglottis (DSE). Results: Among total of 138 patients, 82% fell in easy laryngoscopy and 18% in difficult group. Mallampati and thyromental distance were statistically significant whereas IID showing no difference. The mean DSE in easy group verses difficult group was 1.43 ± 0.27 cm and 2.1 ± 0.22 cm respectively. The accuracy, sensitivity, specificity, PPV and NPV remained higher with DSE measurement techniques as compared to with group as compared to TMD, MPG, IID assessment. The sensitivity and specificity of DSE measurement for prediction of difficult airway was 96% and 97.3%. Conclusions: Ultrasonographic measurement of DSE was better in predicting difficult airway in comparison to other conventional airway assessment methods.